Developing personal finances health measurement index and calculator for young adults based on financial and emotional aspects - Nurulhuda Muhamad Yusof; Masnita Misiran; Hasimah Sapiri; Zahayu Md Yusof; Nor Idayu Mahat; Zainal Akla Shamsudin (Penerbit Universiti Kebangsaan Malaysia, 2025)
Measurement of healthy personal finances is mostly centered on the tangible assets and liabilities assessments, without considering of the emotional aspects that may lead young adults to save (or spend) money based on impulses and other emotional driving factors. This study aims to develop a measurement index to form a personal finances scorecard and calculator that can provide assessment on financial performance among young adults, from the tangible and emotional aspects. The balanced scorecard introduced by Kaplan and Norton (1992) and Yang et al. (2010) will be extended into a proposed personal financial balanced scorecard (PFBSC) to achieve the objective. A financial measurement quadrant is constructed with color-coded scorecard to improve visualization and give better understanding of the result. The findings suggest that the developed scorecard and calculator is easy to use, suitable for young adults, and able to capture both the tangible and emotional aspects of personal finances indicators.